Sol-gel synthesis and characterizations of morphology-controlled Co3O4 particles - Itteboina, Ramakrishna; Sau, Tapan K. (Materials today : proceedings, 2019)
Cobalt oxide particles have emerged as one of the promising metal oxide systems for their unique properties and various applications. This article reports syntheses of nano to micrometer sized morphology-controlled cobalt oxide particles by using the sol-gel synthesis method. The method can produce cobalt oxide particles in gram quantity. We explored the effects of various factors such the metal precursor, capping agent, solvent, calcination temperature, etc. on the size and morphology of the synthesized particles. FTIR and XRD studies confirmed the formation of crystalline Co3O4 particles. Field-emission scanning electron microscopy (FE-SEM) show that particles with sizes ranging from 180 nm to 6 μm and morphologies mainly smoothed surfaced octahedra formed depending on the metal precursor, capping agent, solvent and calcination temperature. The effects of three calcination temperatures have been explored based on the thermal behavior of the particles as studied by the thermogravimetric and differential thermal analysis (TGA/DTA). The powdered particles offer ∼50 to ∼75 m2/g Brunner-Emmett-Teller (BET) surface area. The sol-gel technique is rapid, straightforward, and cost-effective and requires low processing temperatures to produce the particles compared to solvothermal methods. The present study shows that a proper choice of reaction conditions in a sol-gel method could be used to produce morphology-controlled cobalt oxide particles of nanometer to micrometer sizes in high yield.